2019
DOI: 10.17583/remie.2019.4188
|View full text |Cite
|
Sign up to set email alerts
|

Formación de Familiares y Voluntariado. Los Beneficios de la Solidaridad en la Escuela

Abstract: The aim of this article is to analyze the benefits of solidarity promoted by volunteering in family education at various Spanish elementary schools which are Learning Communities. One of the common organization principles in these schools is solidarity, which is visible in various spaces and actions. Among these, volunteers of very diverse profiles are included in family education. The results presented here are part of a broader research project, 'The improvement of the educational system through the family e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 25 publications
0
8
0
1
Order By: Relevance
“…Schools as Learning Communities, an educational model based on community participation through egalitarian dialogue, has been shown to improve, in addition to academic achievements, the school environment and social cohesion [29][30][31]. In particular, different studies on these interactive spaces reported an increase in social inclusion [32,33] and solidarity [34] and a decrease in violence [31,35]. Such outcomes are especially prominent in low SES communities, where the context is transformed through the participation and engagement of a diversity of voices, cultural backgrounds, knowledge, and experiences in an egalitarian dialogue [32,36].…”
Section: Fostering Supportive and Safe Educational Environmentsmentioning
confidence: 99%
“…Schools as Learning Communities, an educational model based on community participation through egalitarian dialogue, has been shown to improve, in addition to academic achievements, the school environment and social cohesion [29][30][31]. In particular, different studies on these interactive spaces reported an increase in social inclusion [32,33] and solidarity [34] and a decrease in violence [31,35]. Such outcomes are especially prominent in low SES communities, where the context is transformed through the participation and engagement of a diversity of voices, cultural backgrounds, knowledge, and experiences in an egalitarian dialogue [32,36].…”
Section: Fostering Supportive and Safe Educational Environmentsmentioning
confidence: 99%
“…Social sciences have made, and are increasingly making, contributions promoting social impact (Aiello et al, 2020 ) in education (Rios-Gonzalez et al, 2019 ; Yeste et al, 2019 ; Duque et al, 2020 ; Ruiz-Eugenio et al, 2020b ), ethnic and cultural minorities (Gómez et al, 2019 ; Khalfaoui, 2019 ; Garcia Yeste et al, 2020 ; Serradell et al, 2020 ), gender, sexuality and masculinities (Foraster and Morlà, 2019 ; Serrano Amaya and Ríos González, 2019 ; Merodio et al, 2020 ; Salceda et al, 2020 ), communication and digital media (Madrid et al, 2020 ; Pulido et al, 2020a , b ; Rodríguez et al, 2020 ) or occupation and organizations (Campos et al, 2020 ; Mara et al, 2020 ; Redondo-Sama, 2020 ; Tellado et al, 2020 ), among others. However, when we look at the scientific and theoretical production throughout the history of social sciences, a great fragmentation can be observed, having little interdisciplinarity and little connection between what authors in the different disciplines are contributing.…”
Section: The Fragmentation Of the Social Sciencesmentioning
confidence: 99%
“…Some of the practices identified and reviewed in this work which addressed the lure of violence (described in subsection 3) are outstanding as they acknowledge the relevance of treating this very aspect in a direct way, and not as a side-issue -collateral for instance to specific material conditions. An example of this is the dialogic model of prevention and resolution of conflicts that is being used in some schools organized as Learning Communities, involving families and community members in the construction of contexts free of violence in which solidarity prevails [68]. The relevant contribution of this model is that through it, children both reject violence and build a shield in front of the perpetrators of violence, thus showing everyone that those who are violent are not the 'machos' but the 'cowards' [56].…”
Section: Plos Onementioning
confidence: 99%